Earth pressure analysis of inclined support structures adjacent to existing structures - Chucai Peng; Xuhui Fu; Weiwei Wang; Rui Yin (PLoS ONE, 2026)
This study investigates the earth pressure acting on inclined support structures adjacent to existing structures by combining laboratory physical model tests with theoretical derivation. Five groups of model tests were conducted at a constant width-to-height ratio of 0.95, with support inclination angles of 0°, 5°, 10°, 15°, and 20°. Particle image velocimetry (PIV) and multi-point earth pressure monitoring were employed to reveal the failure surface development in the finite soil mass and the distribution characteristics of earth pressure behind the wall. Based on the assumptions of straight failure surfaces and circular-arc major principal stress trajectories, the finite soil mass was divided into several zones. Force equilibrium equations were established for horizontal differential elements in each zone, and theoretical models for earth pressure intensity, resultant force, and the point of application of the resultant force were derived. The theoretical results were generally in good agreement with the experimental results and reasonably reflected the distribution characteristics of passive earth pressure in the finite soil mass under inclined support conditions. In particular, the theoretical predictions were in good agreement with the measured values in the principal compression zone in the middle and lower portions of the soil mass. The measured earth pressures at the upper monitoring points were markedly lower because of local wall-soil separation, the inability of cohesionless sand to transmit tensile stress, and wall-soil contact relaxation. Within the experimental validation range, the resultant earth pressure decreased and its point of application generally shifted upward as the support inclination angle increased. In contrast, an increase in the soil friction angle caused the point of application to shift downward. The findings of this study can provide a theoretical reference for the design of inclined support structures in projects adjacent to existing structures.